First-line bevacizumab-containing therapy for HER2-negative metastatic breast cancer: final results from a prospective German study - Schneeweiss, Andreas (Anticancer research, 2016)
Aim: The German ML21165 study evaluated bevacizumab-containing therapy for metastatic breast cancer (mBC) in routine oncology practice. Patients and Methods: Patients received bevacizumab with chemotherapy until disease progression, unacceptable toxicity or consent withdrawal. Pre-specified end-points were safety and efficacy [response rate, progression-free survival (PFS) and overall survival (OS)]. Results: Between May 2007 and September 2009, 865 patients received first-line bevacizumab plus paclitaxel for mBC, of whom 16% were aged ≥70 years and 9% had ECOG performance status of 2 or more. At data cut-off (median of 15.9 months' follow-up), the median PFS was 9.6 months [95% confidence interval (CI)=9.0-10.4 months] and the median OS was 21.6 months (95% CI=19.4-23.5 months). The most common non-haematological adverse drug reactions of grade 3 or more were pain (9%), hypertension (5%), sensory neuropathy (3%) and proteinuria (3%). Prolonged bevacizumab was well-tolerated. Conclusion: The efficacy and safety of first-line bevacizumab-paclitaxel in routine oncology practice is consistent with results from randomized trials.